The Effect of Quality of Human Resources on The Performance of Bandiklat Central Kalimantan Province - Alexandro, Rinto (Universitas Pendidikan Ganesha, 2020)
Government reforms occurring in Indonesia have resulted in a paradigm shift in governance from a centralized paradigm towards decentralization which is characterized by granting broad and real autonomy to the regions. The objective of management of the Civil Servants (PNS) is to ensure the implementation of government tasks and development in an effective and effective with the support of professional, responsible, honest and fair civil servants through coaching that is carried out based on work performance systems and career systems. Civil servants as apparatus resources should be encouraged to have high professionalism and responsiveness to the growing demands and needs of the community. With professional human resource management arrangements are expected to produce high-quality and high-performance apparatus so that the expected organizational goals can be achieved.